The Reception of Neptune’s Discovery in British and American Protestant Theology - Zenon Roskal; Jacek Rodzeń (Studia Historiae Scientiarum)
The discovery of the planet Neptune in 1846, first theoretically and then observationally, was a 19th-century event that went beyond the interests of the narrow group of astronomers of the time. Indeed, the significance of this event is still a subject of interest among historians and philosophers of science. During the period discussed, natural theology played a special cognitive and social role, forming the basis for arguments based on the new knowledge of nature. This article discusses how the discovery of Neptune was received among the community of 19th-century British and American Protestant theologians, who were always open to scientific research and discoveries.